In vitro Exploration of Vasodilation Activity of the Methanol Extract of the Coptosapelta flavescens Korth stem - Khemasili Kosala; Sjarif Ismail; Ika Fikriah; Agustina Rahayu Magdalena (JIMR - Journal of Islamic Medicine Research, 2017)
ABSTRACTIntroduction: Coptosapelta flavescens Korth is a liana plant of the Rubiaceae genus. In East Kalimantan it is known as Akar Tambolekar or Merung. Its stem is ethnobotanically used as herbs to treat high blood pressure but it has not been scientifically proven yet.Method: This study aims to prove the activity of Coptosapelta flavescens stem (BCF) extract as an antihypertensive by using a blood vessels isolated organ model through the action mechanism as a vasodilator. BCF was taken from Paser Regency, East Kalimantan Province. The extraction was macerated using methanol solvent, then concentrated using a vacuum rotavapour at the temperature of 50C. Vasodilator activity was tested using a 3 mm long rat aorta isolated organ with endothel put into Krebs Henselheit solution at 37C, pH 7.4 and fed by carbogen gas. The aorta is contracted using a phenylephrine solution, after the contraction reached its peak and plateaued, the extract solution or the extracts solvent solution (as control) was added cumulatively and the aortic tone activity was observed. The results were expressed in percent of aortic contractility.Results: The results showed that BCF extract caused an increase in the reduction of aortic contractility percentage as extract concentration increase. Conclusion: This proves that BCFs methanol extract can cause vasodilation in blood vessels with endothelium.Keyword: Coptosapelta flavescens, antihypertensive, extract, isolated aorta, vasodilator